Possibility of using alternative fuels in Polish power plants in the context of mercury emissions. (1st May 2021) - Dziok, Tadeusz; Bury, Marcelina; Bytnar, Krzysztof; Burmistrz, Piotr
Highlights: Mercury content in the waste-derived fuels varies within a very wide range. Co-combustion of waste-derived fuels may result in exceeding the emission limits. Mercury content of alternative fuels should be strictly controlled. Appropriate waste management enable the production fuels with suitable Hg content. Abstract: The progressive decarbonisation of industry is leading to a reduction in coal consumption and the substitution for coal with other types of fuels, including waste-derived alternative fuels. These fuels are characterised by high variation in the content of highly toxic mercury. Co-combustion with coal can cause significant emissions, exceeding mercury emission limits. Various alternative fuels (refuse-derived fuel (RDF), waste paper, textiles, plastics, film, tires and their char, and sewage sludge) were examined for mercury content. The mercury content in analysed alternative fuels ranged from 0.4 to 92.0 µg Hg/MJ, with an average of 17.7 µg Hg/MJ. The fuels with the highest mercury content were RDFs (2.0–79.3 µg Hg/MJ) and sewage sludge (42.3–92.0 µg Hg/MJ). An acceptable amount of RDF added to hard coal which would remain within the emission limits was estimated to be 9–24% of the chemical energy in the blend. For sewage sludge, this amount was estimated to be 5–13%. For brown coal, with a much higher mercury content than hard coal, co-combustion with alternative fuels has a positive effect on reducing mercury emissions. It is possible to meet the mercury emission limits with a 95% contribution of the chemical energy coming from RDF. The blending of various types of waste supported by mild pyrolysis of high-mercury waste allows alternative fuels with relatively low mercury content to be produced. Such fuels may contribute a reduction in mercury emissions from coal-fired power plants in Poland.